China’s Increasing Investments and Relationships with Sea Line Countries of Indian Ocean: A Geopolitical Strategy - Shoukat, Saba; Ashraf, Iqra; Ali, Hina; Ali, Muhammad Zeeshan (Pakistan Journal of Humanities and Social Sciences, 2021)
This study aims to investigate how String of Pearls is referred to as a geopolitical strategy adopted by China and a threat to India as India is a growing regional power? China has invested a lot in building its military bases network in the countries of sea lines that are falling on the Indian Ocean. China has also developed commercial facilities and its military bases, which refer to as String of Pearls. This study will find the interest of China in expanding its engagements in the region of the Indian Ocean. China is investing heavily in the construction of ports, roads, military, and commercial bases along with so many huge products in the countries providing China bases to increase its chain of String of Pearls. The study will identify how these investments made by China are paying off back to China. This research paper will cover Chinese investment in Pakistan, Myanmar, Djibouti, Persian Gulf, Strait of Hormuz, Myanmar, Massawa port Eritrea, Iran, Lamu port Kenya, Sri Lanka, Bangladesh, etc.